AN EVALUATION OF STRATEGIC ISSUES AND CHALLENGES FACING SMALL/MEDIUM PALM GROWERS IN RIAU PROVINCE - M.Alkadri Perdana (Politeknik Negeri Bengkalis, 2016)
Abstract: The palm oil is one of the plantation-sectors which has helped impro- ve economic conditions in Indonesia and has proved a powerful tool for povery alleviation. The oil palm has been successfully adapted suit the needs of small/medium growers. This research focuses on an evaluation strategic issues facing small/medium palm oil growers in Indonesia. This research method uses an exploratory case study approach to answer research aims and questions, based on review of relevant literature and interview questions. The PESTLE framework is the main tool used to evaluate strategic issues and challenges. Data has been collected using primary data as qualitative research by conduction semi-structured interviews with palm growers in Indonesia’s Riau Province. The secondary data has been used to a relevant source to research problem before and after collection of the primary data. Research findings suggest Indonesia has a succesfull national cluster of palm oil industries. Keywords: Palm oil, small/medium growers, PESTLE Framework, strategic issues and challenges, national cluster.